A grammar of Pichi - Yakpo, Kofi (Studies in Diversity Linguistics, 2019)
Pichi is an Afro-Caribbean English-lexifier Creole spoken on the island of Bioko, Equatorial Guinea. It is an offshoot of 19th century Krio (Sierra Leone) and shares many characteristics with West African relatives like Nigerian Pidgin, Cameroon Pidgin, and Ghanaian Pidgin English, as well as with the English-lexifier creoles of the insular and continental Caribbean. This comprehensive description presents a detailed analysis of the grammar and phonology of Pichi. It also includes a collection of texts and wordlists. Pichi features a nominative-accusative alignment, SVO word order, adjective-noun order, prenominal determiners, and prepositions. The language has a seven-vowel system and twenty-two consonant phonemes. Pichi has a two-tone system with tonal minimal pairs, morphological tone, and tonal processes. The morphological structure is largely isolating.